ROLE OF MEDIA IN PROPAGATION OF MUSIC: संगीत के प्रचार- प्रसार में संचार माध्यमों की भूमिका - Srivastava, Kinshuk; Gupta, Suyanka (International Journal of Research -GRANTHAALAYAH, 2015)
Drama and theater have probably been the first strong and vibrant mass media of mankind for centuries. Along with the changing times and society, its form and concerns also kept changing. In ancient times, classical theater was royal and folk theater was dictated. In the medieval period, Muslim-Mughal rulers developed and expanded almost all forms of arts. With the change of time and society, the medium of expression and the nature of literature and arts also change. Science made unprecedented progress in the modern period. New inventions took place. The printing press achieved immense success in making literature accessible and as a medium of information communication. Newspapers turned rumors into authentic information and played a very important role in creating a mass movement in our freedom struggle. नाटक और रंगमंच सम्भवतः मनुष्य जाति का पहला और सदियों तक एकमात्र सशक्त एवं जीवन्त जन-माध्यम रहा है। बदलते हुए समय और समाज के साथ-साथ इसके स्वरूप एवं सरोकार भी लगातार बदलते रहे। प्राचीन काल में शास्त्रीय रंगमंच राज्याश्रित था और लोक-रंगमंच जनाश्रित। मध्यकाल में, मुसलमान-मुगल शासकों ने कलाओं के लगभग सभी रूपों का खूब विकास और विस्तार किया। समय और समाज के परिवर्तन से अभिव्यक्ति माध्यम और साहित्य एवं कलाओं के स्वरूप भी बदलते हैं। आधुनिक काल में विज्ञान ने अभूतपूर्व प्रगति की। नए-नए आविष्कार हुए। प्रिंटिंग प्रेस ने साहित्य को जन-सुलभ बनाने और सूचना-संचार के माध्यम के रूप में अपार सफलता प्राप्त की। अखबारों ने अफवाहों को प्रामाणिक सूचनाओं में बदल दिया और हमारे स्वतंत्रता-संग्राम में जनान्दोलन पैदा करने में अत्यंत महत्वपूर्ण भूमिका निभाई।